Discoloration of Ancient Egyptian Mural Paintings by Streptomyces Strains and Methods of Its Removal - Akmal Ali SAKR (International Journal of Conservation Science, 2012)
Streptomyces isolated from mural paintings at Tell Basta and Tanis tombs were identified using 16S rDNA sequencing method. These Streptomyces strains caused discoloration of mural paintings with irreversible red stains of carotenoid pigment. A mixture of n-hexan and acetone (92:8 v/v) was the best solvent for extracting and purification of red pigment from biomass of Streptomyces. Dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) were the most effective in treatment of these red stains without changing the paintings or stone surfaces.